Redescription of Proteocephalus bagri and p. Rhamdiae (Cestoda: Proteocephalidae), parasites of Rhamdia quelen (Siluriformes: Pimelodidae) from South America, with comments on morphological variation - Gil de Pertierra, Alicia A (Folia parasitologica, 2002)
The pimelodid fish Rhamdia quelen (Quoy et Gaimard, 1824) in South America harbours two species of proteocephalid cestodes, Proteocephalus bagri Holcman-Spector et Mañé-Garzón, 1988 and P. rhamdiae Holcman-Spector et Mañé-Garzón, 1988. These species are redescribed based on a detailed morphological study, supported by multivariate analysis (principal component analysis). Features distinguishing these species are: (1) the shape of proglottides, (2) the mean number of testes, (3) the topography of vitelline follicles, (4) the thickness of internal longitudinal musculature, (5) the mean number of uterine branches, (6) the ratio of cirrus pouch length to proglottis width, (7) the shape of ovary in mature and gravid proglottides and (8) the genital pore position in mature proglottides. The specific status of P. bagri and P. rhamdiae is confirmed and neotypes of both species are designated.
Keywords: Cestoda; Principal Component Analysis; Fish Diseases; cestodózy; zvířata; analýza hlavních komponent; Jižní Amerika; Catfishes; Cestode Infections; South America; nemoci ryb; sumci; Animals